The Linkage of El Niño-induced Peat Fires and Its Relation to Current Haze Condition in Central Kalimantan - Nina Yulianti; Kitso Kusin; Daisuke Naito; Masahiro Kawasaki; Osamu Kozan; Kurniawan Eko Susatyo (Journal of Wetlands Environmental Management, 2020)
fires in Indonesia. About thirty percent of the total fires are spread in Central Kalimantan Province. Symptoms of climate change in the form of increasingly frequent weather and extreme climate phenomena support the severity of forest and land fires which results in increased release of air pollution gases. In 2015, the peak fire months had emitted a high concentration of air pollutant gasses and causes hazardous air pollution. This study aims to investigate the latest severe fire occurrence and haze conditions in Central Kalimantan. Hotspot data was from 2006 to 2017, visibility data were from four times of El Niño event, Particle Matter Size 10 (PM 10) data and Pollution Standard Index (PSI) was from very strong El Niño in 2015 comparison to La Niña in 2016/2017. The results showed that the top incidents occurred not only very strong in 2015 but also weak El Niño in 2006. The most of dense hotspots density in the last twelve years (> 50% of fires in the area) found in peatlands in Pulang Pisau, Palangka Raya and Kapuas.  Palangka Raya's case, dangerous of APSI with PM10 concentrations of more than 500 µg m-3 occurred for 2 (two) months, from the end of August to the early of November 2015. The maximum peak concentration of PM10 is as high as 3000 μg m-3, which is higher than other fire years. Based on the data obtained, the haze was blanketed Palangka Raya was getting thicker at the end of October. As a result, visibility is decreasingly limited, only around 200 to 900 m during the peak season and air pollution-related-peat fire. Thus, this severe condition could rose multiple effects, which will exacerbate climate change, environmental sustainability and the livelihoods of thousands of peoples.